Acupuncture for the Treatment of Allergic Rhinitis: A Systematic Review and Meta-Analysis. Issue 1 (January 2015) - Feng, Shaoyan; Han, Miaomiao; Fan, Yunping; Yang, Guangwei; Liao, Zhenpeng; Liao, Wei; Li, Huabin
Background: Because acupuncture may modulate the immune system, it has been proposed as a useful treatment for patients with allergic rhinitis (AR). Here, we assessed the evidence for the clinical efficacy of acupuncture for the management of AR patients by performing a systematic review and meta-analysis of the published literatures. Methods: By searching PubMed, EMBASE, the Cochrane clinical trials database, and the China National Knowledge Infrastructure from 1980 through July 11, 2013, we collected and analyzed the randomized controlled trials (RCTs) of acupuncture for the treatment of AR patients to assess its efficacy and safety. Results: Thirteen full papers that met our inclusion criteria were included, and a total of 2365 participants, including 1126 as treatment group and 1239 as control group, were enrolled. Compared with control group, acupuncture treatment group exerted a significant reduction in nasal symptom scores (weighted mean difference [WMD]: -4.42, 95% confidence interval [CI]: -8.42 to -0.43, p = 0.03), medication scores (WMD: 1.39, 95% CI: -2.18 to -0.61, p = 0005), and serum IgE (WMD: -75.00, 95% CI: -91.17 to -58.83, p < 0.00001). Data relating to Rhinitis Quality of Life Questionnaire (RQLQ) and 36-Item Short-Form (SF-36) component score in included studies were analyzed, which ultimately point to the efficacy of acupuncture treatment in improving quality of life in AR patients. No fatal events were reported in any of the included studies, and no serious systemic reaction, which needed treatment in the hospital, was related to the acupuncture treatment. Conclusion: Our meta-analysis suggests that that acupuncture could be a safe and valid treatment option for AR patients.